STATUS OF SNOWLEOPARD AND PREY SPECIES IN TORKHOW VALLEY, DISTRICT CHITRAL, PAKISTAN - J. U. Din; M. A. Nawaz (Journal of Animal and Plant Sciences, 2011)
The study was conducted from June – October 2007 and was aimed at assessing the status of snow leopard, its major prey base, and the extent of human-snow leopard conflict in northern Chitral (Torkhow Valley). Snow leopard occurrence was conformed through sign surveys using Snow Leopard Information Management System (SLIMS) protocol. Based on the data collected the number of snow leopards in the study area (1022 km²) was estimated to be 2-3 animals. Highest sign density was seen in Shah Junali (12.8/km), followed by Ujnu Gol (5.8) and Ziwar Gol (2.8). Extrapolating these estimates to the entire Chitral District, gives a population estimate of 36 snow leopards for the district. The livestock depredation reports collected from the area reflected 138 cases affecting 102 families (in a period of eight years, 2001-2008), indicating existence of serious human-snow leopard conflicts. Using point count method during the rut season, a total of 429 Himalayan ibex were counted in the area. The ibex is the only wild ungulate and primary prey for snow leopards in the study. Other carnivores recorded from the area included wolf, jackal, and fox. Major threats to the survival of wildlife especially snow leopard are retaliatory killing (shooting, poisoning), poaching, loss of natural prey, habitat degradation (over grazing, fodder and fuel wood collection), and lack of awareness.
Keywords: Snow leopard; ibex; Chitral; Panthera unica.